A Prospective Economic Evaluation of Rapid Endovascular Therapy for Acute Ischemic Stroke. (12th November 2021) - Sevick, Laura K.; Demchuk, Andrew M.; Shuaib, Ashfaq; Smith, Eric E.; Rempel, Jeremy L.; Butcher, Kenneth; Menon, Bijoy K.; Jeerakathil, Thomas; Kamal, Noreen; Thornton, John; Williams, David; Poppe, Alexandre Y.; et al.
ABSTRACT: Background: During the Randomized Assessment of Rapid Endovascular Treatment (EVT) of Ischemic Stroke (ESCAPE) trial, patient-level micro-costing data were collected. We report a cost-effectiveness analysis of EVT, using ESCAPE trial data and Markov simulation, from a universal, single-payer system using a societal perspective over a patient's lifetime. Methods: Primary data collection alongside the ESCAPE trial provided a 3-month trial-specific, non-model, based cost per quality-adjusted life year (QALY). A Markov model utilizing ongoing lifetime costs and life expectancy from the literature was built to simulate the cost per QALY adopting a lifetime horizon. Health states were defined using the modified Rankin Scale (mRS) scores. Uncertainty was explored using scenario analysis and probabilistic sensitivity analysis. Results: The 3-month trial-based analysis resulted in a cost per QALY of 201, 243 of EVT compared to the best standard of care. In the model-based analysis, using a societal perspective and a lifetime horizon, EVT dominated the standard of care; EVT was both more effective and less costly than the standard of care (−91). When the time horizon was shortened to 1 year, EVT remains cost savings compared to standard of care (∼15, 376 per QALY gained with EVT). However, if the estimate of clinical effectiveness is 4% less than that demonstrated in ESCAPE, EVT is no longer cost savings compared to standard of care. Conclusions: Results support the adoption of EVT as a treatment option for acute ischemic stroke, as the increase in costs associated with caring for EVT patients was recouped within the first year of stroke, and continued to provide cost savings over a patient's lifetime. Clinical Trial Registration: NCT01778335